Screening the pandemic response box identified benzimidazole carbamates, Olorofim and ravuconazole as promising drug candidates for the treatment of eumycetoma - Lim, Wilson; Nyuykonge, Bertrand; Eadie, Kimberly; Konings, Mickey; Smeets, Juli; Fahal, Ahmed; Bonifaz, Alexandro; Todd, Matthew; Perry, Benjamin; Samby, Kirandeep; Burrows, Jeremy; Verbon, Annelies; et al. (PLoS neglected tropical diseases, 2022)
Eumycetoma is a chronic subcutaneous neglected tropical disease that can be caused by more than 40 different fungal causative agents. The most common causative agents produce black grains and belong to the fungal orders Sordariales and Pleosporales. The current antifungal agents used to treat eumycetoma are itraconazole or terbinafine, however, their cure rates are low. To find novel drugs for eumycetoma, we screened 400 diverse drug-like molecules from the Pandemic Response Box against common eumycetoma causative agents as part of the Open Source Mycetoma initiative (MycetOS). 26 compounds were able to inhibit the growth of Madurella mycetomatis , Madurella pseudomycetomatis and Madurella tropicana , 26 compounds inhibited Falciformispora senegalensis and seven inhibited growth of Medicopsis romeroi in vitro . Four compounds were able to inhibit the growth of all five species of fungi tested. They are the benzimidazole carbamates fenbendazole and carbendazim, the 8-aminoquinolone derivative tafenoquine and MMV1578570. Minimal inhibitory concentrations were then determined for the compounds active against M . mycetomatis . Compounds showing potent activity in vitro were further tested in vivo . Fenbendazole, MMV1782387, ravuconazole and olorofim were able to significantly prolong Galleria mellonella larvae survival and are promising candidates to explore in mycetoma treatment and to also serve as scaffolds for medicinal chemistry optimisation in the search for novel antifungals to treat eumycetoma.